Academic Factors Related to Student Achievement in a Capstone Food Chemistry Course. Issue 3 (5th July 2018) - Shoulders, Catherine W.; Johnson, Donald M.; O'Bryan, Corliss A.; Crandall, Philip G.
Abstract: The 1st step in successfully intervening with students who may fail a course is to identify them as early as possible in the semester. The objective of this study was to create a model to predict student performance in FDSC 4304, the required capstone Food Chemistry class, using academic performance in prerequisite courses as potential predictors. We analyzed data for 116 undergraduates who completed Food Chemistry (FDSC 4304) between 2008 and 2015. Data included semester of enrollment and grade earned in FDSC 4304; transfer status; grades in prerequisite classes in science, math, and statistics courses and an introductory Food Science course, FDSC 1103; and the students' university GPA at the time of enrollment in FDSC 4304. Cumulative GPA had the strongest significant ( P  < 0.001) positive correlation with FDSC 4304 grade ( r  = 0.64), followed by grade in statistics GPA ( r  = 0.52), FDSC 1103 grade ( r  = 0.45), pre‐requisite chemistry GPA ( r  = 0.44), and biology GPA ( r  = 0.42). When using partial correlations to control for cumulative GPA, only grades in FDSC 1103 (completed by 62.9% of students) were significantly correlated with grades in FDSC 4304. Linear regression indicated cumulative GPA and FDSC 1103 grades explained 35.5% of the variance in FDSC 4304 grades. When cumulative GPA (available for 91.6% of students) alone was regressed on FDSC 4304, it explained 40.6% of the variance for the larger group. Lower cumulative GPAs and FDSC 1103 grades are suggestive but not determinative of potential student struggles in FDSC 4304. Instructors should use cumulative GPAs and introductory food science course grades (either alone or in combination) with actual early course performance measures to identify students in need of additional help.